Effects of hydrogen sulphide on motility patterns in the rat colon. (12th April 2013) - Gil, V; Parsons, SP; Gallego, D; Huizinga, JD; Jimenez, M
<x xml:space="preserve">Abstract</x> Background and Purpose Hydrogen sulphide (H2S) is an endogenous gaseous signalling molecule with putative functions in gastrointestinal motility regulation. Characterization of H2S effects on colonic motility is crucial to establish its potential use as therapeutic agent in the treatment of colonic disorders. Experimental Approach H2S effects on colonic motility were characterized using video recordings and construction of spatio‐temporal maps. Microelectrode and muscle bath studies were performed to investigate the mechanisms underlying H2S effects. NaHS was used as the source of H2S. Key Results Rhythmic propulsive motor complexes (RPMCs) and ripples were observed in colonic spatio‐temporal maps. Serosal addition of NaHS concentration‐dependently inhibited RPMCs. In contrast, NaHS increased amplitude of the ripples without changing their frequency. Therefore, ripples became the predominant motor pattern. Neuronal blockade with lidocaine inhibited RPMCs, which were restored after administration of carbachol. Subsequent addition of NaHS inhibited RPMCs. Luminal addition of NaHS did not modify motility patterns. NaHS inhibited cholinergic excitatory junction potentials, carbachol‐induced contractions and hyperpolarized smooth muscle cells, but did not modify slow wave activity. Conclusions and Implications H2S modulated colonic motility inhibiting propulsive contractile activity and enhancing the amplitude of ripples, promoting mixing. Muscle hyperpolarization and inhibition of neurally mediated cholinergic responses contributed to the inhibitory effect on propulsive activity. H2S effects were not related to changes in the frequency of slow wave activity originating in the network of interstitial cells of Cajal located near the submuscular plexus. Luminal H2S did not modify colonic motility probably because of epithelial detoxification.